Dietary DHA Regulated the Androgen Production in Male Chinese Tongue Sole Cynoglossus semilaevis - Jiahao Liu; Qiang Ma; Feiran Zhang; Qingyan Gao; Zhijun Zhang; Yuliang Wei; Mengqing Liang; Houguo Xu (Aquaculture Nutrition)
Long-chain polyunsaturated fatty acids (LC-PUFA) play key roles in sex steroid hormone synthesis in fish. Regarding docosahexaenoic acid (DHA), currently the regulating effects were mostly evaluated in female fish rather than males. This study aimed to investigate the DHA effects on the sex steroid hormone production in male Chinese tongue sole. Three experimental diets were prepared, containing different DHA levels: a control (C) group (5.16% DHA of total fatty acids [TFA]), a low DHA group (DHA-L, 8.93%), and a high DHA group (DHA-H, 16.47%). A 58-day feeding experiment was conducted, and each diet was fed to triplicate tanks of fish. Additionally, an in vitro study with Leydig’s cells of this species was conducted to validate the in vivo results. The concentration of testosterone (T) and 11-ketotestosterone (11-KT) in the serum increased with increasing levels of dietary DHA. Dietary DHA significantly upregulated the expression of steroid hormone biosynthetic genes p450c17, hsd17b1, hsd3b1, aromatase, hsd11b2, and p45011b in the testis. The protein expression of Hsd17b1 in the testis of the DHA-H group was significantly higher compared to the other two groups, while the expression level of P450c17 showed an increasing trend with increasing dietary DHA levels. However, the in vitro results confirmed that the final concentration of DHA at 50 μmol/L could significantly increase the gene expression of p450c17 in Leydig’s cells. In conclusion, dietary DHA may promote the synthesis of T and 11-KT through the regulation of protein (Hsd17b1 and P450c17) and gene (p450c17, hsd17b1, hsd3b1, aromatase, hsd11b2, and p45011b) expression of a series of key steroid hormone biosynthetic enzymes in male Chinese tongue sole.